2011
DOI: 10.4103/0971-5916.90987
|View full text |Cite
|
Sign up to set email alerts
|

′First we go to the small doctor′: First contact for curative health care sought by rural communities in Andhra Pradesh & Orissa, India

Abstract: Background & objectives:Against the backdrop of insufficient public supply of primary care and reports of informal providers, the present study sought to collect descriptive evidence on 1st contact curative health care seeking choices among rural communities in two States of India - Andhra Pradesh (AP) and Orissa.Methods:The cross-sectional study design combined a Household Survey (1,810 households in AP; 5,342 in Orissa), 48 Focus Group Discussions (19 in AP; 29 in Orissa), and 61 Key Informant Interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 14 publications
10
39
0
Order By: Relevance
“…Our study confirmed the findings of several other studies (Rohde and Vishwanathan 1995; Gautham et al 2011; George and Iyer 2013; Das et al 2012) that IPs are a significant source of basic health care for rural residents. A study of IPs in two other Andhra districts, Warangal and Karimnagar, located in the state’s Telengana region, also reported ‘doorstep’ services (Gautham et al 2011) by mobile IPs who travelled from house to house and village to village on their daily service delivery rounds.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirmed the findings of several other studies (Rohde and Vishwanathan 1995; Gautham et al 2011; George and Iyer 2013; Das et al 2012) that IPs are a significant source of basic health care for rural residents. A study of IPs in two other Andhra districts, Warangal and Karimnagar, located in the state’s Telengana region, also reported ‘doorstep’ services (Gautham et al 2011) by mobile IPs who travelled from house to house and village to village on their daily service delivery rounds.…”
Section: Discussionsupporting
confidence: 92%
“…These providers tend to be viewed as a homogenous group, but studies in different settings suggest that they differ, in terms of education and training, the contents of their practice and their business model (Gautham et al 2011; George and Iyer 2013). They work in complex health markets and are influenced by many factors, which include consumer expectations, relationships with other providers and formal and informal rules (George and Iyer 2013; Bloom et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Patients tend to move from one provider to another before they are finally properly diagnosed by a specialist and given proper treatment [6, 15, 16]. This was also true with our patients, who spent some time looking for the right eye specialist and/or whose diagnosis was sometimes delayed due to controversial doctors' opinions from different healthcare providers.…”
Section: Discussionmentioning
confidence: 64%
“…Private and informal HCPs are often the first source of care for any illness 6-8 and also TB. 9 There is evidence, albeit limited, that patients with TB symptoms often begin seeking advice in the informal private sector (chemists and unqualified practitioners), then seek care from qualified practitioners, and eventually end up in the public sector for free treatment.…”
Section: Introductionmentioning
confidence: 99%